Evaluation of bacterial susceptibility to carbapenems of strains isolated from patients in an adult intensive care unit - Keila Takano OLIVIERI; Vedilaine Aparecida MACEDO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: To describe bacterial susceptibility to carbapenems prescribed to inpatients in the adult intensive care unit (ICU) at public hospital in São Paulo. Methods: This is a descriptive and retrospective study of the release reports of treatment with carbapenems and consultations to laboratory tests, including 81 reports and 129 cultures from 70 patients. Data collection was based on patients admitted to the adult intensive care unit of a Municipal Public Hospital who received carbapenem antibiotics from July to September 2021. Results: A total of eighty-one reports for carbapenem treatment in the intensive care unit were analyzed. Male sex prevailed (65.4%). The mean age of patients in the study was 63 ± 15 years. In 59 (72.8%) of the reports, meropenem was used and in the other 22 (27.2%) cases imipenem-cilastatin was prescribed. Empirical therapy was reported in most reports (57/81), 3 reports were incompleted, and 21 reports were specific therapy. In twenty-four cultures, gram-positive bacteria were identified and in forty-six cultures, gram-negative bacteria were identified. Klebsiella pneumoniae was the most prevalent pathogen identified in 15 samples, followed by Pseudomonas aeruginosa (12). Resistance to meropenem was identified in 15 gram-negative samples, while 16 gram negative strains were resistant to imipenem. Conclusion: The results of this study indicated a high prevalence of Klebsiella pneumoniae followed by Acinetobacter baumani, and a high rate of resistance to carbapenems. Thus, it is necessary to periodically update empirical therapy protocols based on the knowledge of the nosocomial microbiota, to prevent bacterial resistance, because the development of resistance mechanisms against antimicrobial compounds is constant.